Effect of Brazilian Propolis on Exacerbation of Respiratory Syncytial Virus Infection in Mice Exposed to Tetrabromobisphenol A, a Brominated Flame Retardant - Takeshita, Tomomi (Hindawi Publishing Corporation, 2013)
Tetrabromobisphenol A (TBBPA), a brominated flame retardant, has been found to exacerbate pneumonia in respiratory syncytial virus- (RSV-) infected mice. We examined the effect of Brazilian propolis (AF-08) on the exacerbation of RSV infection by TBBPA exposure in mice. Mice were fed a powdered diet mixed with 1% TBBPA alone, 0.02% AF-08 alone, or 1% TBBPA and 0.02% AF-08 for four weeks and then intranasally infected with RSV. TBBPA exposure increased the pulmonary virus titer and level of IFN-γ, a representative marker of pneumonia due to RSV infection, in the lungs of infected mice without toxicity. AF-08 was significantly effective in reducing the virus titers and IFN-γ level increased by TBBPA exposure. Also, AF-08 significantly reduced proinflammatory cytokine (TNF-α and IL-6) levels in the lungs of RSV-infected mice with TBBPA exposure, but Th2 cytokine (IL-4 and IL-10) levels were not evidently increased. Neither TBBPA exposure nor AF-08 treatment affected the anti-RSV antibody production in RSV-infected mice. In flow cytometry analysis, AF-08 seemed to be effective in reducing the ratio of pulmonary CD8a(+) cells in RSV-infected mice with TBBPA exposure. TBBPA and AF-08 did not exhibit anti-RSV activity in vitro. Thus, AF-08 probably ameliorated pneumonia exacerbated by TBBPA exposure in RSV-infected mice by limiting excess cellular immune responses.